Impact Of Macroeconomic Variables And Zakat On Poverty Alleviation: Evidence From Indonesian Panel Data Analysis - Jaya, Tiara Juliana; Meylianingrum, Kurniawati; Aghniacakti, Ainindita; Kholilah, Kholilah; Syariati, Dian (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2025)
Purpose: This study examined the impact of macroeconomic variables and zakat on poverty alleviation.Design/methodology: This study is a quantitative study with a regression analysis method of panel data in districts/cities in Central Java, West Java, and East Java, from 2018 to 2022. Additional testing on a subsample in East Java was conducted to ensure the consistency of the results.Findings: The findings indicate that the Human Development Index, gross domestic product, and zakat negatively affect poverty levels, while the regional minimum wage positively affects poverty alleviation. Further, the study fails to find any significant impact of government expenditure on poverty alleviation. The test in East Java indicates that only the regional minimum wage and government expenditure affect poverty levels. This suggests that poverty is a complex issue that varies from region to region, necessitating region-specific poverty alleviation policies.Practical implications: These results suggest that the synergy between government and society is crucial for poverty alleviation in Indonesia, and policies should be tailored to the specific conditions of each region.Originality/Value: This study provides insights into the complex relationship between macroeconomic variables and poverty alleviation, highlighting the regional differences in the impact of these variables.